Pilot hole study in friction stir welding processes: A review - Nur Syafiqah, Sofian; Luqman Hakim, Ahmad Shah (Universiti Malaysia Pahang, 2024)
This paper reviews the progress of research on the use of pilot holes in metal joints during welding, focusing on Friction Stir Welding and Friction Stir Spot Welding (FSSW) processes. The impact of pilot holes on the mechanical behaviour and macrostructure of metal joints under various welding conditions was thoroughly evaluated. The incorporation of pilot holes in FSSW processes, particularly for similar aluminum alloy joints, can increase mechanical performance by up to 50%. This technique also enhances tool longevity, improves joint quality, and optimizes surface finish. Several factors influenced by pilot hole optimisation are discussed, including the significance of the pilot-hole-to-keyhole (PTK) diameter ratio. Notably, pilot holes with a PTK ratio below 1 have demonstrated superior results. In dissimilar material FSSW, pilot hole conditions significantly influence material flow and intermixing, thereby affecting joint strength. Additionally, the diameter of the pilot hole plays a critical role in the welding process, significantly affecting joint integrity. Based on these findings, several recommendations are offered to guide future research and application in this field, including an exploration of the relationship between the PTK ratio and its influence on material flow to enhance mechanical performance and joint quality.